Role of fibroblast growth factor signalling in hepatic fibrosis - Seitz, Tatjana; Hellerbrand, Claus (Liver International, 2021)
Fibrotic remodelling is a highly conserved protective response to tissue injury and it is essential for the maintenance of structural and functional tissue integrity. Also hepatic fibrosis can be considered as a wound-healing response to liver injury, reflecting a balance between liver repair and scar formation. In contrast, pathological fibrosis corresponds to impaired wound healing. Usually, the liver regenerates after acute injury. However, if the damaging mechanisms persist, the liver reacts with progressive and uncontrolled accumulation of extracellular matrix proteins. Eventually, excessive fibrosis can lead to cirrhosis and hepatic failure. Furthermore, cirrhosis is the major risk factor for the development of hepatocellular cancer (HCC). Therefore, hepatic fibrosis is the most critical pathological factor that determines the morbidity and mortality of patients with chronic liver disease. Still, no effective anti-fibrogenic therapies exist, despite the very high medical need. The regulation of fibroblast growth factor (FGF) signalling is a prerequisite for adequate wound healing, repair and homeostasis in various tissues and organs. The FGF family comprises 22 proteins that can be classified into paracrine, intracrine and endocrine factors. Most FGFs signal through transmembrane tyrosine kinase FGF receptors (FGFRs). Although FGFRs are promising targets for the treatment of HCC, the expression and function of FGFR-ligands in hepatic fibrosis is still poorly understood. This review summarizes the latest advances in our understanding of FGF signalling in hepatic fibrosis. Furthermore, the potential of FGFs as targets for the treatment of hepatic fibrosis and remaining challenges for the field are discussed.
CRIS-Team Scopus Importer:2021-04-02
Keywords: FGF; fibroblast growth factors; fibrosis; hepatic stellate cells; wound healing